CONCEPT ISTIQĀMAH IN SURAT FUṢṢILAT VERSES 30-31 WITH MA'NĀ CUM MAGHZĀ APPROACH - Idris Idris; Shobichatul Muniroh (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2021)
The main goal of istiqāmah for a Muslim is to be consistent with his Islam, but, in Indonesia, many Muslims are still not quite right in understanding the true meaning of istiqāmah. Among them, understanding istiqāmah is only limited to doing certain practices and stopping at one point of practice (not dynamic).Using the ma'nā cum maghzā approach, this article critically presents the initial understanding ma'nā of the word istiqāmah in Surat Fuṣṣilat: 30-31 through historical context analysis (macro and micro) and linguistic analysis (intratextuality and intertextuality). After ma'nā analysis, we are exploring the main message when Surat Fuṣṣilat: 30-31 is necessary. This is verses was revealed, then continued by drawing new understanding (reinterpretation) to find the main message that is universal and relevant to the current context.In this research, there are several findings, namely: a) al-ma’nā al-tārikhī from istiqāmah is luzum al-thā'at (but obedience), b) al-maghzā al-tārikhī from Surat Fuṣṣilat: 30-31 is whatever the challenge or test faced by believers should not diminish their faith and obedience to Allah, and c) al-maghzā almutaḥarrik from the verse explains that the concept of istiqāmah that is patiently bearing various consequences of faith., as well as implementing Rabbunā Allāhi in moderate ritual piety (shari'at) and social piety (akhlaq).